Progressive muscle relaxation in pandemic times: bolstering medical student resilience through IPRMP and Gagne's model - Nair, Bhavana; Khan, Sara; Naidoo, Nerissa; Jannati, Shirin; Shivani, Balamohan; Banerjee, Yajnavalka (Frontiers in Psychology, 2024)
Background: Medical education, already demanding, has been further strained by the COVID-19 pandemic's challenges and the shift to distance learning. This context underscores the need for effective stress reduction techniques in competency-based medical curricula (CBMC).We assessed the feasibility and benefits of integrating a Progressive Muscle Relaxation (PMR) module-a known effective stress-reducing technique-into a time-restricted CBMC, particularly given such modules often find placement as elective rather than mandatory.Methods: Adapting Gagne's nine events of instruction, a two-hour PMR program was designed and implemented during the pandemic. Twenty participants were engaged on a first-come, first-served basis, ensuring adherence to social distancing measures. Feedback was continuously gathered, leading to two post-program focus group sessions. Qualitative data underwent thematic analysis following Braun and Clarke's approach, with study quality maintained by the Standards for Reporting Qualitative Research (SRQR). To gauge adaptability, we aligned the program with various learning outcomes frameworks and explored its fit within CBMC using Bourdieu's Theory of Practice.The pilot PMR program was well-received and effectively incorporated into our CBMC. Our analysis revealed five central themes tied to PMR's impact: Self-control, Self-realization, Liberation, Awareness, and Interpersonal relationships. Feedback indicated the program's capacity to mitigate stress during the pandemic. The SRQR confirmed the study's alignment with qualitative research standards. Further, the PMR program's contents resonated with principal domains of learning outcomes, and its integration into CBMC was supported by Bourdieu's Theory. These observations led us to propose the Integrative Psychological Resilience Model in Medical Practice (IPRMP), a model that captures the intricate interplay between the identified psychological constructs. Conclusion: This research showcases an innovative, theory-guided approach to embed a well-being program within CBMC, accentuating PMR's role in fostering resilience among medical students. Our PMR model offers a feasible, cost-effective strategy suitable for global adoption in medical institutions. By instilling resilience and advanced stress-management techniques, PMR ensures that upcoming healthcare professionals are better equipped to manage crises like pandemics efficiently.